2016
DOI: 10.1146/annurev-nutr-071715-050725
|View full text |Cite
|
Sign up to set email alerts
|

Reward Systems in the Brain and Nutrition

Abstract: The taste cortex in the anterior insula provides separate and combined representations of the taste, temperature, and texture of food in the mouth independently of hunger and thus of reward value and pleasantness. One synapse on, in the orbitofrontal cortex, these sensory inputs are combined by associative learning with olfactory and visual inputs for some neurons, and these neurons encode food reward value in that they respond to food only when hunger is present and in that activations correlate linearly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 192 publications
(371 reference statements)
2
70
0
2
Order By: Relevance
“…A recent review suggests that water has limitations as a comparison since it can activate taste regions. (Rolls, 2016) Participants in the current study rated water as more palatable than sucrose, suggesting water may not be a neutral stimulus. While some studies have shown discrimination between sugar and water in the insula(Schoenfeld et al, 2004) others have not,(Rolls, 2005; Wagner et al, 2008; Zald et al, 2002) potentially due to methodological differences.…”
Section: Discussionmentioning
confidence: 75%
“…A recent review suggests that water has limitations as a comparison since it can activate taste regions. (Rolls, 2016) Participants in the current study rated water as more palatable than sucrose, suggesting water may not be a neutral stimulus. While some studies have shown discrimination between sugar and water in the insula(Schoenfeld et al, 2004) others have not,(Rolls, 2005; Wagner et al, 2008; Zald et al, 2002) potentially due to methodological differences.…”
Section: Discussionmentioning
confidence: 75%
“…136 Although self-control as a psychological construct has historically been a subject of inquiry, [137][138][139] the identification of specific brain systems involved has been ongoing for only a few decades. The predominant foci in neuroimaging research are reward signaling mechanisms 140 and reward-modulating control systems. 13,14 Investigations involving fMRI consistently link food-cue related activations of the limbic system with height-ened weight and or body composition, as discussed earlier.…”
Section: The Social Neurobiology Of Food Consumptionmentioning
confidence: 99%
“…Other orbitofrontal cortex neurons neurons represent the expected reward value of olfactory stimuli, based on similar evidence (Rolls and Baylis 1994, Critchley and Rolls 1996b, Rolls, Critchley, Mason and Wakeman 1996, Critchley and Rolls 1996a. Reward Outcome is represented in the orbitofrontal cortex by its neurons that respond to taste and fat texture (Rolls, Yaxley and Sienkiewicz 1990, Rolls and Baylis 1994, Rolls, Critchley, Browning, Hernadi and Lenard 1999, Verhagen, Rolls and Kadohisa 2003, Rolls, Verhagen and Kadohisa 2003b, and do this based on their reward value as shown by the fact that their responses decrease to zero when the reward is devalued by feeding to satiety (Rolls, Sienkiewicz and Yaxley 1989, Rolls, Critchley, Browning, Hernadi and Lenard 1999, Rolls 2015b, Rolls 2016c. Moreover, the primate orbitofrontal cortex is key in these reward value representations, for it receives the necessary inputs from the inferior temporal visual cortex, insular taste cortex, and pyriform olfactory cortex, yet in these preceding areas reward value is not represented (Rolls 2014, Rolls 2015b, Rolls 2015a.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%